The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.2903/j.efsa.2019.5638
|View full text |Cite
|
Sign up to set email alerts
|

Lumpy skin disease

Abstract: In 2018, no lumpy skin disease (LSD) outbreaks were reported in the Balkan region, after the decline reported in 2017 (385) compared to 2016 (7,483). This confirms the effectiveness of the vaccination campaign based on the LSD homologous vaccine strain which continued throughout 2018 with over 2.5 million animals vaccinated, keeping the mean vaccination coverage above 70%. In 2018, LSD outbreaks were reported in Russia, Turkey and Georgia. In Russia, the LSD epidemics expanded northward and eastward, while in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 32 publications
(53 reference statements)
0
9
0
Order By: Relevance
“…Various efficacy studies mainly based on small-scale challenge studies have been published which generally indicate homologous vaccines confer higher rates of protection compared to heterologous although one study provided some evidence of comparable efficacy using the Gorgan goat pox strain (56,57). Analysis of the recent LSD outbreak in Europe in 2014-2018 provided evidence that vaccination programmes based on the Neethling strain of LSDV were very effective at controlling the disease (32,58). A randomised field trial in Israel also demonstrated relative superior efficacy of the homologous vaccine (59).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various efficacy studies mainly based on small-scale challenge studies have been published which generally indicate homologous vaccines confer higher rates of protection compared to heterologous although one study provided some evidence of comparable efficacy using the Gorgan goat pox strain (56,57). Analysis of the recent LSD outbreak in Europe in 2014-2018 provided evidence that vaccination programmes based on the Neethling strain of LSDV were very effective at controlling the disease (32,58). A randomised field trial in Israel also demonstrated relative superior efficacy of the homologous vaccine (59).…”
Section: Discussionmentioning
confidence: 99%
“…Most currently available vaccines are live attenuated and contain either LSDV (homologous) or sheep and goat pox strains (heterologous) (11,31). Heterologous vaccines are generally considered to be less effective but with fewer side effects particularly in European breeds of cattle (32).…”
Section: Introductionmentioning
confidence: 99%
“…According to Israeli experience, the LSD Nt vaccine caused only mild adverse effects at a very low incidence (0.38-0.6%) [21]. In Croatia, adverse reactions were reported in 0.09% of the vaccinated animals using a homologous vaccine [23]. In a study carried out by Greek scientists, a local reaction at the vaccination site was detected in 12% and generalized small-sized lumps in 9% of animals vaccinated with a commercially available LSD Nt strain vaccine [22].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, lumpy skin disease has expanded its geographic range out of Africa into the Middle East to Eastern Europe and Asia (7,11). Most recently, LSDV spread in the Balkans including, Greece, Bulgaria, Serbia, Kosovo, Albania, Montenegro, the Caucasus Region including Russia, and Asian countries of Kazakhstan and recently China (11,12). The rapid spread of LSDV into previously free regions is cause for concern, since if not effectively dealt with through using mass vaccination with an effective vaccine, LSDV will spread into bordering regions through either animal movement or dispersion of insect vectors (11).…”
mentioning
confidence: 99%
“…Control of sheep and goatpox can be achieved through slaughter of infected animals. Unfortunately with LSDV slaughter is not effective and can only be achieved using live attenuated vaccines (1,2,17); illustrated by mass vaccination of cattle in Eastern Europe where vaccination has eliminated clinical disease (6,12).…”
mentioning
confidence: 99%